A paediatric pain assessment and management survey at Rahima Moosa Mother and Child Hospital, Johannesburg, South Africa - L M N Mabaso; A Bhettay; R Bandini; D Demopoulos (South African Medical Journal, 2022)
Background. Painful experiences are common in the paediatric inpatient population. Immaturity and cognitive impairment may preclude clear description of such experiences, and requests for analgesia when needed. Methods of pain assessment and guidelines for treatment in the paediatric population are well established, but are not widely used. Limited data suggest that the situation is similar in South Africa (SA). Objectives. To review the assessment and management of pain in SA medical paediatric inpatients. The primary objective was to determine the proportion of children who receive analgesia where indicated. The secondary objectives were to determine the prevalence of pain, at presentation and among admitted patients, whether pain evaluations were performed and pain treated, and the adequacy of such treatment. Methods. A prospective cross-sectional survey of medical paediatric inpatients at Rahima Moosa Mother and Child Hospital (RMMCH) in Johannesburg, SA, was conducted. The tool used for data collection was specifically designed for the study, with sections for demographic data, patient or caregiver interview, and chart review. Pain assessments were done using the revised Face, Legs, Activity, Cry, Consolability Scale and the Neonatal/Infant Pain Scale. The analysis consisted of descriptive statistics of epidemiological data and comparative statistics using grouped variables, with the level of significance set at p<0.05. Results. The sample consisted of 74 children, aged between 3 days and 4 years. Male patients accounted for 58% of the cohort. The prevalence of pain at admission was 73% (n=53). Eight percent (n=6) of the study sample had pain evaluation at admission, and only 1 child had been evaluated for pain within the preceding 24 hours. Of the 74 patients reviewed, 10% (n=7) received appropriate analgesia. Paracetamol was given to 31% of patients (n=23), either for pyrexia or for an undocumented indication. More than half of the study sample (59%; n=44) received no analgesia. The presence of pain, both by caregiver report (p=0.62) and by pain score (p=0.074), was not associated with the administration of analgesia. Conclusion. Pain in the paediatric population at RMMCH was found to be common, but it was seldom assessed, and validated pain scores were rarely used. The result was inadequate pain management in all the four domains of assessment, intervention, reassessment and ongoing management.